Effects of bamboo biochar on nitrogen conservation during co-composting of layer manure and spent mushroom substrate. Issue 25 (10th November 2022) - Zhang, Bangxi; Fan, Beibei; Hassan, Iram; Peng, Yutao; Ma, Ruonan; Guan, Chung-Yu; Chen, Shili; Cui, Shihao; Li, Guoxue
ABSTRACT: Layer manure (LM) and spent mushroom substrate (SMS) are two kinds of nitrogen (N) rich solid wastes generate in the poultry breeding and agriculture production. Composting is an effective way to recycle the LM and SMS. However, a large amount of N in the LM and SMS was lost via volatilisation during composting, with negative environmental and economic consequences. This study investigated the effect of incorporating biochar at the ratio of 5%, 10%, and 15% ( w/w ) during co-composting of LM and SMS on ammonia (NH3 ) and nitrogen oxide (N2 O) volatilisation and N retention. After the 35-day composting, the results showed that the pile temperature and seed germination index in biochar treatments were significantly improved in comparison with control treatment. The nitrogen in all treatments was lost in the form of N2 O (0.05∼0.1%) and NH3 (13.1∼20.2%). Likewise, the total nitrogen loss was 28.9%, 20.3%, and 24.9%, respectively, of which N2 O-N accounts for 0.05∼0.10%. Compared with control treatment, the total amount of NH3 volatilisation in biochar treatments of 5%BC, 10%BC and 15%BC was decreased by 21.2%, 33.1%, and 26.1%, respectively. The total amount of N2 O emission was decreased by 39.0%, 13.2%, and 1.6%, respectively. Adding 10% and 15% biochar can significantly reduce NH3 volatilisation while adding 5% biochar treatment didn't significantly reduce NH3 emissions but showed the best performance in reducing N2 O emission. The addition of 10% biochar in co-composting of LM and SMS is the recommended dosage that exhibited the best performance in improving composting quality and reducing nitrogen loss. GRAPHICAL ABSTRACT: UF0001